Peran Komunikasi Persuasif Dalam Membina Kedisiplinan Siswa Di SMPN 17 Oku Desa Marga Mulya Kabupaten Ogan Komering Ulu - Iha Nur Kharimah; Fifi Hasmawati; Manalullaili (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This research was carried out in Marga Mulya Village, Ogan Komering Ulu Regency, the problem raised was the role of persuasive communication in fostering student discipline at SMPN 17 OKU. This research aims to determine the role of persuasive communication so that it can influence students and what discipline and persuasive techniques are used so that students in educational institutions can be influenced by disciplinary attitudes, and what inhibiting factors occur in students. This research uses qualitative descriptive research, while the data collection techniques during the research process show that there are several observation and interview methods. The results of this research show that there are several roles of persuasive communication, namely the role of persuader of a group of people who convey a message with the aim of influencing attitudes, persuade the person to whom the message is delivered/distributed, perception of the message conveyed will determine the effectiveness of the communicant, persuasive message as a conscious effort to change thoughts and actions by directing motivation towards predetermined goals, persuasive channels that act as intermediaries when students are persuaded to convey messages from the original source to the final destination such as WhatsApp group media and others, feedback and response effects or responses that come from communicator or from the message itself. The persuasive communication techniques include the communication message association technique by superimposing it on an object or event that is interesting to the audience, the integration technique where the strength in building student discipline is seen from the communicator's ability to unite himself communicatively with the communicant, the red herring technique, namely giving a warning. about their parents who had put them through school with great difficulty. In essence, persuasive communication here is about inviting or persuading students to instill a disciplined attitude.